‘Three warnings and you’re out’: Banishment and precarious penality in South Africa’s informal settlements - Super, Gail (Punishment & society, 2020)
This paper asks how punitive forms of non-state punishment play out on the margins of the state, in informal (shack) settlements in South Africa. My focus is on the practice of forcing those who are suspected of certain offences to leave their homes in informal settlements. I refer to this as ‘banishment’ and argue that it is a ‘penal phenomenon’ which is intimately tied to the general precarity that residents experience on a daily basis. The paper examines the ways in which these formally illegal, but nonetheless legitimate practices, draw on and reconfigure liberal state punishment. I use my study to make a broader theoretical point about the interplay between lawful state punishment and unlawful punishment on the periphery of the state. The blurred boundaries between legal (state) violence and illegal (but nonetheless legitimate) violence are particularly ‘visible’ in situations of ‘precarious penality’ - a term that I use to describe the unstable, violent and exclusionary penality that manifests in situations of socio-economic precarity, particularly in contexts of inequality, high rates of violent crime and a delegitimated rule of law. In these circumstances ‘non-state’ punishment contributes to the construction and maintenance of group boundaries and fulfils a similar function to ‘formal’ punishment. Thus, I ask whether it makes sense to exclude ‘non-state’ public authorities which act against ‘criminality’, when asking what or who constitutes the penal field and, when measuring state punitiveness?